DNA copy number alterations mark disease progression in paediatric chronic myeloid leukaemia - Van Der Sligte, Naomi E.; Krumbholz, Manuela; Pastorczak, Agata; Scheijen, Blanca; Tauer, Josephine T.; Nowasz, Christina; Sonneveld, Edwin; De Bock, Geertruida H.; Meeuwsen-De Boer, Tiny G. J.; Van Reijmersdal, Simon; Kuiper, Roland P.; Bradtke, Jutta; et al. (British Journal of Haematology, 2014)
Early recognition of children with chronic phase chronic myeloid leukaemia (CML-CP) at risk for developing a lymphoid blast crisis (LyBC) is desirable, because therapy options in CML-LyBC are limited. We used Multiplex Ligation-dependent Probe Amplification to determine whether B-cell lymphoid leukaemia-specific copy number alterations (CNAs) (e.g. IKZF1, PAX5, CDKN2A deletions) could be detected in CML-CP and may be used to predict disease progression to LyBC. CNAs were detected in all patients with CML-LyBC, but in none of the 77 patients with CML-CP. Based on this study we conclude that CNAs remain a hallmark of disease progression.
EVALuna2:18891